Colonoscopy and Histopathologic Features in Chronic Diarrhea Patients at Dr. Hasan Sadikin General Hospital, Bandung - Rasdianto, Devi Novianto; Nugraha, Eka Surya; Usman, Hermin Aminah; Agustanti, Nenny; Wahyudi, Yudi; Girawan, Dolvy; Bestari, Muhammad Begawan; Abdurachman, Siti Aminah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Diagnosing and managing patients with chronic diarrhea remains a clinical challenge due to its broad differential diagnoses. Colonoscopy with biopsy is often indicated to establish chronic diarrhea etiologies. However, to date, no data have been published describing the colonoscopic and histological findings in patients with chronic diarrhea at Dr. Hasan Sadikin General Hospital in Bandung. This study aimed to determine the features of colonoscopy and histology in patients with chronic diarrhea.Methods: This study employed a cross-sectional-descriptive design, utilizing secondary data from colonoscopy examinations conducted at Dr. Hasan Sadikin Hospital General Hospital from 2016 to 2019. Participants included adults aged 18 and above who had been diagnosed with chronic diarrhea and had completed both colonoscopy and biopsy procedures.Results: A total of 182 subjects with chronic diarrhea were included in the study. The majority were women (52%), with mean age of 46 years. Upon admission, the predominant clinical presentation was chronic diarrhea without hematochezia, observed in 75% of cases. Meanwhile, 52% of colonoscopy lesions were multiple, with the anal-rectum segment (15%) being the most involved. The most frequent colonoscopic features were hyperemic or edematous lesions, seen in 58% of subjects. The histopathological result from this study revealed that 59% were non-specific chronic colitis (NSCC). Specific histopathological features were primarily found in malignancies and inflammatory bowel disease (IBD) that is 14% 12%, respectively.Conclusion: Chronic diarrhea without hematochezia was the most common objective for referring patients to colonoscopy. The most frequently observed lesion was hyperemic mucosa. Moreover, the NSCC was frequent in histopathological evaluation, followed by malignancies and IBD .